Avaliação da condição estrutural de danos em pontes através de dados de vibração - Braido, Jorge Dalmas (2022)
Damages are considered a phenomenon which has more than one source in structures. On bridges, visual inspection is the main source of data and helps to identify, analyze and assess the structures’ actual condition. Although, this procedure has faults already known as the capacity to discover only apparent damages. Structural Health Monitoring, also known as SHM, shows visual inspection as the first investigation procedure on the methodology. To overcome this negative characteristic, usually natural frequencies, modal shapes damping rates, peak-to-peak acceleration are used to describe the structural dynamic behavior. This research has experimental and numerical phases which are composed by finite element models, acceleration samples extracted through a cell phone, sampling rates correction, smartphone calibration, damage indexes which considers the peak-to-peak acceleration magnitude and natural frequency variation. The main focus is to assess the structural condition from more than one damage indicator. Study cases are two bridges, in Passo Fundo/RS, and one T cross-section beam in reinforced concrete. Results shows that is possible to assess the Brazilian concrete bridges formed by two cantilever girders and deck installed on the highway system since 1940. Moreover, shows the necessity to use more than one damage index to define damages.